THE RELATION OF THE ABILITY OF IMPERATIVE SENTENCES AND THE WRITING SKILL OF JUNIOR HIGH SCHOOL STUDENTS - Rico Mandela; Jenny Elvinna Manurung; Farnia Sari (Didascein : Journal of English Education, 2022)
One of the texts used in daily life is procedure text which requires imperative sentences to accomplish writing procedure texts. Procedure text is one of many short functional texts in writing that should be mastered by the students in ninth grade learning English. Thus, this study aims to find out whether there was a significant correlation or not between the ability of imperative sentences and the writing skill of procedure text. The population was ninth-grade students with a total of 67 students at SMP Azhariah Palembang. For the sample of this study, the intake sampling technique was used to take the sample with 67 students. The data were obtained from students’ imperative sentence scores and their writing procedure text scores. In analyzing the data, correlation analysis was used. Based on the statistical analysis, it was found that the correlation coefficient or the r-value (0.294) was higher than the r-table (0.236). It can be concluded that there was a correlation between the ability of imperative sentences and the writing skill of procedure text. Some students had a minimum level of imperative sentence test but they were able to create good writing procedure tests. Some other factors might influence their result in the two tests such as their concentration, experience, habit in writing, etc.